Paracooperia nodulosa infection in a water buffalo (Bubalus bubalis) calf - Sheikh Omar, Abdul Rahman; Ikeme, M. M.; I., Fatimah (BMJ Publishing Group, 1985)
ONE of the most pathogenic trichostrongylids of the water buffalo (Bubalus bubalis) is Paracooperia nodulosa, which gives rise to formation of multiple nodules in the intestine,diarrhoea, anaemia, emaciation and sometimes death (Mohan 1968). The disease has been reported in many countries but is especially common in Bulgaria, India and Pakistan (Sharma and Pande 1963, Mohan 1968, Griffiths 1974). In Malaysia, the parasite was reported in cattle and buffalo as Cooperia nodulosa but without any mention of the disease it caused (Euzeby ] 956, Lancaster 1958) and there has not been any report since